Inflation Targeting Monetary Policy and Unemployment in South Africa - Harris Maduku; Irrshad Kaseeram (Journal of Economics and Behavioral Studies, 2018)
We analyze the impact of inflation, growth and exchange rate on unemployment in South Africa using annual data spanning 1980- 2017. Using the ARDL methodology we find that there is a negative longrun relationship between inflation and unemployment in South Africa and inflation is significant in explaining unemployment. Other variables of interest, economic growth and exchange rate are also significant in explaining unemployment. We use the findings of our study to propose that the South African Reserve Bank(SARB) should consider revising its objectives so that they can consider getting involved in targeting unemployment so that they help nurse the economy from the wounds of high inequality and poverty.